2001
DOI: 10.1063/1.1337863
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio studies of the reactions of M(1S,3P, and 1P) with GeH4 (M=Cd, Hg)

Abstract: Ab initio studies of the reactions of Cu ( 2 S, 2 D, and 2 P) with SiH 4 and GeH 4The interaction of Cd( 1 S:5s 2 , 3,1 P:5s 1 5p 1 ) and Hg( 1 S:6s 2 , 1,3 P:6s 1 6 p 1 ) with GeH 4 were studied by means of Hartree-Fock self-consistent field ͑SCF͒ and multiconfigurational SCF plus variational and multireference second order Möller-Plesset perturbational configuration interaction ͑CIPSI͒ calculations, using relativistic effective core potentials. It was found that both metal atoms in their 3 P(ns 1 np 1 ) stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…This behavior is similar to the HCuSiH 3 intermediate product formation in the Cu+ CH 4 and Cu + SiH 4 interactions previously studied. This state is found to be responsible for the Si-H bond activation of the SiH 4 molecule and also the relaxation involved in the C s HAuSiH 3 intermediate product formation.…”
Section: Discussionsupporting
confidence: 87%
“…This behavior is similar to the HCuSiH 3 intermediate product formation in the Cu+ CH 4 and Cu + SiH 4 interactions previously studied. This state is found to be responsible for the Si-H bond activation of the SiH 4 molecule and also the relaxation involved in the C s HAuSiH 3 intermediate product formation.…”
Section: Discussionsupporting
confidence: 87%
“…Luna-García et al [11] have found that mercury in its excited state ( 1 P: 5d 10 6s 1 6p 1 ) breaks the Ge-H bond of germane, while forming a ground state barrier of 86.1 kcal mol −1 . The experimental transition energy between the excited state ( 1 P: 5d 10 6s 1 6p 1 ) and the ground state ( 1 S: 5d 10 6s 2 ) amounts to 154.6 kcal mol −1 , in good agreement with the transition energy of 157.6 kcal mol −1 theoretically calculated (Table 2(c)).…”
Section: Amentioning
confidence: 99%
“…Transition probabilities for the interaction of the lowest excited states of the metal X with tetrahedral gas molecules are studied through one-dimensional Landau-Zener theory. The strategy for obtaining the reaction pathways for X + YH 4 interactions has been extensively used in references [8][9][10][11][12][13][14] based on the original proposal by Chaquin et al [15]. The initial approach (starting from 20 a.u.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation